Advances in service-oriented and cloud computing : workshops of ESOCC 2014, Manchester, UK, September 2-4, 2014, Revised selected papers /: workshops of ESOCC 2014, Manchester, UK, September 2-4, 2014, Revised selected papers. (2015) - Unknown
No abstract available